Water requirements of cowpea (Vigna unguiculata (L.) Walp.). calculated with the cultivation coefficient using drainage lysimeter - Chavarria Parraga, Jesus Enrique; Ugando Peñate, Mikel; Sabando García, Angel Ramon; Muñoz Parraga, Jean Pierre; Bravo Ferrín, Richard Xavier; Villalón Peñate, Antonio (Universidad Pedagógica y Tecnológica de Colombia, 2020)
The objective is to estimate the water needs of the cowpea (Vigna unguiculata L.) var. INIAP-463 from the culture coefficient using drainage lysimeter. It was carried out in the months of January to April 2018, three plots of 25m2 were implemented, and drainage lysimeters were located in the center of them. The plots were placed near the meteorological station located at the Pontificia Universidad Católica del Ecuador Sede Manabí. The data of the climatological variables were used to estimate the reference evapotranspiration (ETo) by the Penman Monteith method modified by the FAO. Daily monitoring of the drainage sheet of the lysimeter and soil moisture present in it. The irrigation sheet was applied daily, based on the daily ETo and the rainfall of the place. The calculation of the Kc was carried out for each stage of the culture, determining the ratio between the evapotranspiration of the culture (ETc) and ETo. The Kc values ​​for the bean were: first stage with a duration of 15 days a Kc of 0.45 was obtained, second stage 20 days a Kc of 0.88, third stage 25 days a Kc of 1.28, fourth stage 20 days a Kc of 0.70. The water requirement of the cowpea was greater in the third stage with 114.33 mm and the one with the lowest consumption was the first stage with 20.46, the total water need was 254 mm for 80 days after transplantation. The results found allow us to conclude that the water needs of the cowpea var. INIAP-463 were higher in the third stage of cultivation due to the presence of organs of vegetative reproduction and abundant leaf area.